Triboelectric Nanogenerators: Development of a High‐Performance Handheld Triboelectric Nanogenerator with a Lightweight Power Transmission Unit (Adv. Mater. Technol. 4/2020). Issue 4 (14th April 2020) - Choi, Seonbeen; Cho, Sumin; Yun, Yeongcheol; Jang, Sunmin; Choi, Jun Hyuk; Ra, Yoonsang; La, Moonwoo; Park, Sung Jea; Choi, Dongwhi
Abstract : In article number 2000003, Sung Jea Park, Dongwhi Choi and co‐workers present the development of a high‐performance handheld triboelectric nanogenerator (TENG). With adoption of a rationally designed lightweight mechanical power transmission unit, the simple finger pressing motion generates dramatically enhanced electrical output performance from the TENG and thus, it can be utilized as a potential portable power source for powering portable electronics without spatiotemporal limitation.